Effects of Acute Respiratory and Metabolic Acidosis on Diaphragm Muscle Obtained from Rats. (April 2015) - Michelet, Pierre; Carreira, Serge; Demoule, Alexandre; Amour, Julien; Langeron, Olivier; Riou, Bruno; Coirault, Catherine
<x xml:space="preserve">Abstract</x> Background: Acute respiratory acidosis is associated with alterations in diaphragm performance. The authors compared the effects of respiratory acidosis and metabolic acidosis in the rat diaphragm in vitro. Methods: Diaphragmatic strips were stimulated in vitro, and mechanical and energetic variables were measured, cross-bridge kinetics calculated, and the effects of fatigue evaluated. An extracellular pH of 7.00 was obtained by increasing carbon dioxide tension (from 25 to 104 mmHg) in the respiratory acidosis group (n = 12) or lowering bicarbonate concentration (from 24.5 to 5.5 mM) in the metabolic acidosis group (n = 12) and the results compared with a control group (n = 12, pH = 7.40) after 20-min exposure. Results: Respiratory acidosis induced a significant decrease in maximum shortening velocity (−33%, P < 0.001), active isometric force (−36%, P < 0.001), and peak power output (−59%, P < 0.001), slowed relaxation, and decreased the number of cross-bridges (−35%, P < 0.001) but not the force per cross-bridge, and impaired recovery from fatigue. Respiratory acidosis impaired more relaxation than contraction, as shown by impairment in contraction–relaxation coupling under isotonic (−26%, P < 0.001) or isometric (−44%, P < 0.001) conditions. In contrast, no significant differences in diaphragmatic contraction, relaxation, or contraction–relaxation coupling were observed in the metabolic acidosis group. Conclusions: In rat diaphragm, acute (20 min) respiratory acidosis induced a marked decrease in the diaphragm contractility, which was not observed in metabolic acidosis.